1996
DOI: 10.1080/01635589609514440
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sucrose, glucose, fructose, and starches affect colonic functions in rats

Abstract: To study the effect of dietary sugars and starches on parameters linked to colon carcinogenesis, female Sprague-Dawley rats were fed for one month five different diets containing sucrose, glucose, fructose, cornstarch, or Hylon 7, a starch with a high amylose content. After this period, colon proliferation, assessed by [3H] thymidine incorporation in vitro, was higher (p < 0.05) in rats fed sucrose than in rats fed glucose, fructose, or cornstarch [labeling index was 7.17 +/- 0.75, 5.03 +/- 0.07, 4.55 +/- 0.72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…Animal and human studies have shown that manipulation of diet and other lifestyle exposures result in adaptive changes in the colon crypt epithelium and in TGF-α expression specifically (17, 21, 22, 24, 25). Our preliminary findings suggest that TGF-α levels may vary according to modifiable dietary risk factors (intake of sucrose, low-fat dairy, fruits, and vegetables), and although, in this small sample, few differences were statistically significant, many are consistent with current hypotheses about diet, growth, and colorectal cancer (7, 14, 17, 20, 24, 25, 35, 4448). Furthermore, associations between TGF-α expression and risk for adenoma were strengthened following adjustment for risk factors, suggesting that a person with elevated TGF-α levels could further increase or decrease their probability of being a case (that is, risk for incident sporadic colorectal adenoma) based on their history of risk behaviors, such as use of NSAIDs or total energy intake.…”
Section: Discussionsupporting
confidence: 75%
“…Animal and human studies have shown that manipulation of diet and other lifestyle exposures result in adaptive changes in the colon crypt epithelium and in TGF-α expression specifically (17, 21, 22, 24, 25). Our preliminary findings suggest that TGF-α levels may vary according to modifiable dietary risk factors (intake of sucrose, low-fat dairy, fruits, and vegetables), and although, in this small sample, few differences were statistically significant, many are consistent with current hypotheses about diet, growth, and colorectal cancer (7, 14, 17, 20, 24, 25, 35, 4448). Furthermore, associations between TGF-α expression and risk for adenoma were strengthened following adjustment for risk factors, suggesting that a person with elevated TGF-α levels could further increase or decrease their probability of being a case (that is, risk for incident sporadic colorectal adenoma) based on their history of risk behaviors, such as use of NSAIDs or total energy intake.…”
Section: Discussionsupporting
confidence: 75%
“…Consequently, an elevated dietary level of fructose (460 g kg À1 ) produced a low caecal concentration of SCFA, and of the same magnitude as an identical level of glucose. 39 In the present study, caecal weights for rats fed apples tended to be higher than for the other groups (data not shown), suggesting that some amounts of fructose might have added to the amount of indigestible carbohydrates reaching the rat hindgut. Fructosecontaining oligosaccharides such as Neosugar 11 and inulin 40,41 have been found to give high proportions of butyric acid in the rat caecum.…”
Section: Discussionmentioning
confidence: 75%
“…2000b; Ferguson et al . 2000), reduce faecal and/or caecal pH (Caderni et al . 1996; Cassand et al .…”
Section: Resistant Starch and Colonic Function (Colorectal Cancer Inmentioning
confidence: 99%